Balance and effectiveness of research and innovation spending : Government and UK Research and Innovation Responses to the Committee's Twenty-First Report of Session 2017–19 : First Special Report of Session 2019-21 /: Government and UK Research and Innovation Responses to the Committee's Twenty-First Report of Session 2017–19 : First Special Report of Session 2019-21. ([2020-06-02]) - Unknown
No abstract available